Self-adaptive molybdenum disulfide-based multi-layer composite film resistant to low orbit space irradiation and preparation method of self-adaptive molybdenum disulfide-based multi-layer composite film

A multilayer MoS2-based composite film with controlled layering and composition addresses the radiation-induced wear of sputtered MoS2 films, achieving low friction and extended wear life in low-orbit satellite environments.

CN119243098AActive Publication Date: 2025-01-03SHANGHAI AEROSPACE EQUIPMENTS MANUFACTURER CO LTD

Patent Information

Application Number
CN202411235936.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-03
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

Existing sputtered MoS2 films used in satellite moving parts fail to withstand low-orbit space radiation, leading to rapid wear and decreased toughness due to radiation-induced vacancies and amorphous structure formation, which compromises their lubrication performance.

Method used

A multilayer composite film structure comprising a Ti bonding layer, MoS2-Ti gradient transition layer, MoS2-Ti functional layer, MoS2-Ti-C transition layer, and MoS2-C functional layer is deposited using magnetron sputtering, with controlled thickness and composition to maintain a low friction coefficient and enhance toughness.

Benefits of technology

The composite film exhibits a friction coefficient below 0.02 and wear life exceeding 3.0×10^5 cycles in a vacuum environment, effectively resisting low-orbit space radiation and ensuring long-term reliability of satellite moving parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243098A_ABST
    Figure CN119243098A_ABST
Patent Text Reader

Abstract

The invention relates to the field of solid lubricating materials of aerospace materials, and particularly discloses a self-adaptive molybdenum disulfide-based multi-layer composite film resistant to low orbit space irradiation and a preparation method of the self-adaptive molybdenum disulfide-based multi-layer composite film. The closed field unbalanced magnetron sputtering technology is adopted, and a bonding layer (Ti), a gradient transition layer (MoS2 / Ti), a functional layer (MoS2 / Ti), a transition layer (MoS2-Ti-C) and a functional layer (MoS2-C) are deposited on a metal material to form the multi-layer composite lubricating film. The prepared lubricating film can reliably serve in a low-orbit space environment, can effectively reduce mechanical abrasion of space mechanical friction moving parts, and can still keep stable tribological performance under long-time irradiation in the low-orbit space. The method is particularly suitable for long-term moving parts such as bearings and gears of new-generation low-orbit service spacecrafts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of aerospace material solid lubricating materials, and specifically relates to an adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation and a preparation method thereof. Background Art

[0002] Large low-orbit constellations are aerospace systems that have emerged and gradually matured in the last 10 years. They are composed of hundreds to tens of thousands of satellites operating in space 300km to 2000km above the ground.

[0003] Solid lubricating film is the key to ensure the long-term reliable service of the moving parts of satellite structures in low-orbit environments. There are many types of solid lubricants currently used in satellite moving parts. Among them, sputtered MoS2 has a lamellar structure and a very low friction coefficient under vacuum. It is currently the most widely used and successful lubricating material for precision sliding moving parts in space.

[0004] The main reason for the failure of sputtered MoS2 films in space environment is directly related to the space radiation environment. Space radiation mainly includes space ultraviolet radiation, atomic oxygen erosion, high-energy particle radiation (electrons, protons), etc. With the continuous development of space exploration activities, in order to meet the long-term service requirements of spacecraft in low orbits, sputtered MoS2 films must meet the ability to withstand low-orbit space radiation. Studies have shown that a large number of vacancies agglomerate to form large-sized voids during the irradiation process of MoS2 films, and the film becomes severely amorphous after the irradiation damage is greater than 5dpa. Radiation hardening leads to a decrease in the toughness of the film. At the same time, the irregular transfer of disordered structures at the friction interface is worse than that of unirradiated samples, resulting in the ordered transfer film being quickly pushed out of the contact surface during the friction process, and the wear life rapidly decreases by 1-2 orders of magnitude.

[0005] Therefore, improving the space radiation resistance of sputtered MoS2 films in low orbit is the key to realizing the application of this material system in low-orbit satellites.

[0006] Through searching the existing patent documents, it is found that CN 115323326 A discloses a long-life molybdenum disulfide-based composite film resistant to space atomic oxygen irradiation, and its preparation method and application, which belongs to the field of solid lubrication technology. The Ti layer can increase the bonding strength between the molybdenum disulfide-based composite film and the substrate. The Ti content in the MoS2-LaF3-Ti layer located on the surface of the Ti layer is 6-10% at%, and the LaF3 content is 2-4 at%. Ti and LaF3 exist in the form of solid solution, which greatly reduces the sensitivity of MoS2 to atomic oxygen, significantly improves the anti-proton oxygen irradiation performance and wear-resistant life of the composite film, reduces the friction coefficient, and effectively solves the problem that the wear-resistant life of the molybdenum disulfide film decreases sharply under the erosion of high-dose space atomic oxygen. However, the thickness of the MoS2-LaF3-Ti composite film in this technology is between 2 and 5 μm, which cannot meet the requirements of 1 μm film of sputtered molybdenum disulfide film thickness for parts such as space precision bearings and harmonics. According to the adhesive wear characteristics of molybdenum disulfide, the film thickness is highly correlated with the film lubrication life. In addition, the MoS2-LaF3-Ti film in the invention has different components from those in the present invention. CN202311541172 discloses a wear-resistant molybdenum disulfide-based composite film and a preparation method thereof, which uses composite magnetron sputtering technology to deposit a molybdenum disulfide-based solid lubricating film on the surface of a 316L stainless steel substrate, and controls the content of Ti in the functional layer MoS2-Ti so that Ti exists in the form of a solid solution. Without destroying the layered structure and lubrication properties of the MoS2 film, the sensitivity of MoS2 to the environment and the friction coefficient are greatly reduced, and the wear life of the MoS2 composite film is significantly improved. The composite film includes a Ti metal ion implantation layer, a Ti metal transition layer, and a MoS2-Ti functional layer from the substrate surface to the outside. Patent CN20161103338 discloses a molybdenum disulfide-lead-titanium alloy nano-multilayer film and a preparation method thereof, which includes a Ti transition layer, a gradient transition layer of Ti and molybdenum disulfide, an alternating multilayer formed by alternating superposition of molybdenum disulfide and lead-titanium alloy, and a molybdenum disulfide surface layer. The film has a large dry friction coefficient under vacuum environment, which is stably maintained at 0.02-0.06. CN202010497699 discloses a method for preparing a sub-10 nanometer bionic structure molybdenum disulfide-carbon multilayer film, in which a molybdenum disulfide layer is prepared by a high-power pulsed unbalanced magnetron sputtering method on the treated substrate component, and then a high-pressure plasma immersion ion implantation technology is used to inject CH4 plasma with a purity greater than 99.99% into the molybdenum disulfide layer to form a carbon layer, which is repeated for 40-80 cycles, and the thickness of each layer is controlled below 10nm. This scheme adopts a nano-laminated structure, which is not only complex in process, but also involves core issues such as sub-layer interface bonding, and no specific limitations are given. It can be foreseen that the repeatability is poor. Summary of the invention

[0007] In view of the above problems, the purpose of the present invention is to provide an adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation and a preparation method. The prepared molybdenum disulfide-based composite film can serve reliably on the surface of moving parts exposed to the space environment in low orbit, has a low friction coefficient and can adapt to the low-orbit space radiation environment, can effectively reduce the mechanical wear of frictional moving parts of space machinery, and can greatly improve the reliability of mechanical moving parts exposed to space.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides an adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation, and the film structure includes a deposited Ti bonding layer, a MoS2-Ti gradient transition layer, a MoS2-Ti functional layer, a MoS2-Ti-C transition layer, and a MoS2-C functional layer in order from near to far from the substrate. The friction coefficient of the composite film of the deposited Ti bonding layer + MoS2-Ti gradient transition layer + MoS2-Ti functional layer + MoS2-Ti-C transition layer + MoS2-C functional layer of the present invention is between 0.016 and 0.18, which is less than 0.2. The mechanism is that carbon and molybdenum disulfide will form a heterojunction structure during the friction process, reducing the friction coefficient. And under this film layer structure, as the friction time increases, the wear of the lubricating film layer deepens, and the carbon adhered to the surface of the dual part will still form a heterojunction structure with the underlying molybdenum disulfide at the friction interface, and thus always show a low friction coefficient. In the multilayer composite film of the present invention, a MoS2-Ti gradient transition layer is provided to reduce the thermal expansion coefficient between the metal and molybdenum disulfide on the one hand, and to enhance the hardness and toughness of the molybdenum disulfide film on the other hand; if the MoS2-Ti gradient transition layer (Ti content is 0-40at%) is replaced by a Ti metal transition layer (Ti content is 100at%), it will show poor film-base bonding and short wear life. If the multilayer composite film is set as a deposited Ti bonding layer + MoS2-Ti gradient transition layer + MoS2-Ti functional layer, the purpose of the present invention cannot be achieved, and the friction coefficient of the structure is close to 0.2, greater than 0.2. For another example, the film structure is designed as a deposited Ti bonding layer + MoS2-Ti-C transition layer + MoS2-C functional layer, which still cannot achieve the purpose of the present invention; it is mainly manifested in poor friction and wear life; taking Example 1 of the present invention as an example, the friction and wear life of the deposited Ti bonding layer + MoS2-Ti gradient transition layer + MoS2-Ti functional layer + MoS2-Ti-C transition layer + MoS2-C functional layer is 3.1×10 5 The friction and wear life of the deposited Ti bonding layer + MoS2-Ti-C transition layer + MoS2-C functional layer is 6×10 4 change.

[0010] As an embodiment of the present invention, the thickness of the film is 1 to 5 μm.

[0011] As an embodiment of the present invention, the thickness of the deposited Ti bonding layer is 100-500 nm.

[0012] As an embodiment of the present invention, the thickness of the MoS2-Ti gradient transition layer is 100 to 1000 nm.

[0013] As one embodiment of the present invention, the thickness of the MoS2-Ti functional layer is 200 to 2000 nm.

[0014] As one embodiment of the present invention, the thickness of the MoS2-Ti-C transition layer is 50 to 500 nm.

[0015] As an embodiment of the present invention, the thickness of the MoS2-C functional layer is 50 to 1000 nm. In practice, the thickness and number of each layer of the composite film layer are determined according to specific requirements.

[0016] As one embodiment of the present invention, the Ti content in the MoS2-Ti gradient transition layer is 0 to 40 at%.

[0017] As one embodiment of the present invention, the Ti content in the MoS2-Ti functional layer ranges from 8% to 20%.

[0018] As one embodiment of the present invention, the MoS2-Ti-C gradient transition layer has a C content of 10 to 50 at%, and a Ti content of 5 to 12 at%.

[0019] As one embodiment of the present invention, the C content in the MoS2-C functional layer is 40 to 50 at%.

[0020] The present invention also provides a method for preparing the adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation described in the above technical solution, comprising the following steps:

[0021] S1. Plasma cleaning, laser cleaning or high temperature drying cleaning of metal parts;

[0022] S2, using a titanium target to deposit a Ti bonding layer on the surface of a metal substrate by magnetron sputtering;

[0023] S3, using titanium target and molybdenum disulfide target to deposit MoS2-Ti gradient transition layer by magnetron sputtering;

[0024] S4, using a titanium target and a molybdenum disulfide target to deposit a MoS2-Ti functional layer by magnetron sputtering;

[0025] S5, using titanium target, molybdenum disulfide target and graphite target to deposit MoS2-Ti-C gradient transition layer by magnetron sputtering;

[0026] S6. Depositing MoS2-C functional layer by magnetron sputtering using molybdenum disulfide target and graphite target.

[0027] In step S1, plasma cleaning has three main purposes: a. Remove the natural oxide scale and excess materials on the surface of the test piece; b. Clean the target surface; c. Activate the surface of metal parts, increase the active sites on the metal surface, and increase the bonding force between the film and the substrate. Technically, laser cleaning and high-temperature drying cleaning can also be used. Compared with other technologies, the process temperature of plasma cleaning body substrate contaminants is low.

[0028] The process gases that can be used in plasma cleaning also include oxygen, argon, nitrogen, compressed air, carbon dioxide, hydrogen, carbon tetrafluoride, etc. As an embodiment of the present invention, in step S1, the plasma cleaning is to introduce argon at a pressure lower than 1×10-3Pa, and use a linear ion source to clean the metal substrate.

[0029] As an embodiment of the present invention, the power of the linear ion source is 2-4 kW, and the cleaning time is 20-60 min.

[0030] As an embodiment of the present invention, in steps S1-S6, closed field unbalanced magnetron sputtering technology is used. In step S1, the bias voltage is 350-500 V. In step S2, the bias voltage is set to 70-110 V. In steps S3-S6, the bias voltage is set to 40-80 V respectively.

[0031] As an embodiment of the present invention, in step S2, the titanium target current is 0.5 to 5 A, and the deposition time is 10 to 60 min.

[0032] As an embodiment of the present invention, in step S3, the titanium target current is constant within the range of 1A to 5A, the molybdenum disulfide target current is linearly increased from 0.1A to 4A, and the deposition time is 10 to 60 minutes. The constant refers to a current value that is constant within the range of 1A to 5A.

[0033] As an embodiment of the present invention, in step S4, the titanium target current is constant within the range of 1A to 5A, the molybdenum disulfide target current is constant within the range of 1A to 4A, and the deposition time is 10 to 120 minutes.

[0034] As an embodiment of the present invention, in step S5, the molybdenum disulfide target current is constant in the range of 1A to 4A, the graphite target current increases linearly from 0.1A to 3A, the titanium target current decreases to 0A, and the deposition time is 2 to 60 minutes.

[0035] As an embodiment of the present invention, in step S6, the molybdenum disulfide target current is constant in the range of 1A to 4A, the graphite target current is constant in the range of 0.8 to 3A, and the deposition time is 5 to 120 minutes.

[0036] As an embodiment of the present invention, the purity of the Ar gas introduced during plasma cleaning is ≥99.999%; the purity of the Ti target is ≥99.6%, the purity of the molybdenum disulfide target is ≥99.6%, and the purity of the graphite target is >99.6%.

[0037] The present invention also provides the use of the adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation described in the above technical solution as a solid lubricant for aerospace materials. It is particularly suitable for use as a solid lubricant for long-term moving parts such as bearings and gears of a new generation of spacecraft serving in low-orbit.

[0038] Compared with the prior art, the present invention has the following excellent effects:

[0039] 1) The present invention adopts closed-field unbalanced magnetron sputtering technology to prepare a bonding layer (Ti), a gradient transition layer (MoS2-Ti), a functional layer (MoS2-Ti), a transition layer (MoS2-Ti-C), and a functional layer (MoS2-C) lubricating film deposited in sequence on the surface of a metal substrate.

[0040] 2) The present invention controls the target current, argon gas flow rate and other factors during the growth of the lubricating film by regulating the process parameters, and accurately prepares the molybdenum disulfide-based multilayer composite film.

[0041] 3) On the one hand, adding an appropriate amount of carbon element to the molybdenum disulfide film can promote the evolution of the friction interface into a highly ordered heterogeneous contact interface during movement. The incommensurate contact of the heterogeneous contact interface reduces the friction coefficient by orders of magnitude, and has better lubrication performance under a vacuum environment; on the other hand, the addition of carbon elements can improve the toughness of the composite film and reduce the hardening effect of long-term irradiation on the composite film.

[0042] 4) The prepared composite film was exposed to a total atomic oxygen radiation of 7.8×10 26 pcs / m 2 、Total UV radiation 8000ESH, ionizing radiation 2×10 8 rad(Si), the friction and wear life in vacuum environment is greater than 3.0×10 5 r, the friction coefficient is less than 0.02. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0044] Figure 1 Schematic diagram of the structure of sputtered molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation. DETAILED DESCRIPTION

[0045] The present invention provides an adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation, the structure of which is as follows: Figure 1 As shown, the film structure includes a bonding layer (Ti), a gradient transition layer (MoS2-Ti), a functional layer (MoS2-Ti), a gradient transition layer (MoS2-Ti-C), and a functional layer (MoS2-C) in order from near to far from the substrate. Among them, the thickness of the Ti bonding layer is 100-500nm; the thickness of the MoS2-Ti gradient transition layer is 100-1000nm, and the Ti content is 0-40at%; the MoS2-Ti functional layer is 200-2000nm; the MoS2-Ti-C transition layer is 50-500nm, the C content is 10-50at%, and the Ti content is 5-12at%; the MoS2-C functional layer is 50-1000nm, and the C content is 40-50at%. The thickness and number of each layer of the composite film layer are determined according to specific requirements.

[0046] The method for preparing the adaptive molybdenum disulfide-based multilayer composite film of the present invention may include the following steps:

[0047] Step 1: Plasma cleaning: clean the metal parts and put them into the vacuum furnace. -3 When Pa, argon gas is introduced, and the metal substrate is cleaned by a linear ion source, the power of the linear ion source is 2-4 kW, and the time is 20-60 min;

[0048] Step 2, bonding layer deposition: using a titanium target to magnetron sputter and deposit a bonding Ti layer on the surface of the metal substrate, preferably, the titanium target current is 0.5 to 5A, and the time is 10 to 60 minutes;

[0049] Step 3, gradient transition layer deposition: using titanium target and molybdenum disulfide target to magnetron sputter and deposit gradient transition MoS2-Ti layer, the titanium target current is constant, and the molybdenum disulfide target current is linearly increased from 0.4A to 4A, and the time is 10 to 60min;

[0050] Step 4: Deposition of functional layer: Deposition of functional MoS2-Ti layer by magnetron sputtering using titanium target and molybdenum disulfide target respectively, with constant current of titanium target and molybdenum disulfide target for 10 to 120 min;

[0051] Step 5: Deposition of transition layer: Deposition of transition MoS2-Ti-C layer by magnetron sputtering using titanium target, molybdenum disulfide target and graphite target respectively, the current of molybdenum disulfide target is constant, the current of graphite target increases linearly from 0.1A to 3A, and the current of titanium target decreases to 0A, and the time is 2 to 60min;

[0052] Step 6, functional layer deposition: using a molybdenum disulfide target and a graphite target for magnetron sputtering deposition of a functional MoS2-C layer, respectively, the molybdenum disulfide target current and the graphite target current are constant, and the time is 5 to 120 minutes.

[0053] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0054] Example 1

[0055] The method for preparing the adaptive molybdenum disulfide-based multilayer composite film of this embodiment comprises the following steps:

[0056] Step 1: Plasma cleaning: clean the titanium alloy TC4 metal parts and put them into the vacuum furnace. -3 When Pa, argon gas was introduced, and the metal substrate was cleaned by a linear ion source with a power of 3 kW, a time of 20 min, and a bias voltage of 400 V;

[0057] Step 2, bonding layer deposition: using a titanium target to deposit a bonding Ti layer on the surface of the metal substrate by magnetron sputtering, the titanium target current is 3A, the time is 10min, and the bias voltage is 80V;

[0058] Step 3, gradient transition layer deposition: using titanium target and molybdenum disulfide target magnetron sputtering to deposit gradient transition MoS2-Ti layer, the titanium target current is constant at 3A, and the molybdenum disulfide target current is linearly increased from 0.4A to 2A, the time is 10min, and the bias voltage is 70V;

[0059] Step 4: Deposition of functional layer: Deposition of functional MoS2-Ti layer by magnetron sputtering using titanium target and molybdenum disulfide target, respectively, with a constant current of 3A for titanium target and a constant current of 2A for molybdenum disulfide target, for 40 min and a bias voltage of 70 V;

[0060] Step 5: Gradient transition layer deposition: The transition MoS2-Ti-C layer was deposited by magnetron sputtering using titanium target, molybdenum disulfide target and graphite target respectively. The current of the molybdenum disulfide target was constant, the current of the graphite target was linearly increased from 0.1A to 1A, and the current of the titanium target was linearly decreased from 3A to 0A. The time was 2min and the bias voltage was 70V.

[0061] Step 6, functional layer deposition: the functional MoS2-C layer was deposited by magnetron sputtering using a molybdenum disulfide target and a graphite target, respectively. The molybdenum disulfide target current was constant at 2A, the graphite target current was constant at 1A, the time was 20min, and the bias voltage was 70V.

[0062] The lubricating film deposited in this embodiment has a bright and smooth gray-black coating surface. The thickness of the lubricating film tested by a three-dimensional optical profilometer is 1±0.1μm, wherein the thickness of the Ti bonding layer is 100±10nm; the thickness of the MoS2-Ti gradient transition layer is about 150±15nm; the MoS2-Ti functional layer is 550±55nm; the MoS2-Ti-C transition layer is 50±5nm, with a C content of 12at%, and a Ti content of 8at%; the MoS2-C functional layer is 150±15nm, with a C content of 45at%. Referring to GJB2502.9-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 9: Atomic Oxygen Test", the total atomic oxygen irradiation for 15 years of simulated on-orbit flight on the ground is 7.8×10 26 pcs / m 2 ; According to GJB2502.5-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 5: Vacuum Ultraviolet Irradiation Test", after the total ultraviolet irradiation is 8000ESH, a ball-disc friction and wear tester is used. According to GJB3032-97 "Specifications for Sputtered MoS2-based Self-lubricating Solid Films", the friction and wear life in vacuum environment is 3.1×10 5 r, the friction coefficient is 0.018.

[0063] Example 2

[0064] The method for preparing the adaptive molybdenum disulfide-based multilayer composite film of this embodiment comprises the following steps:

[0065] Step 1: Plasma cleaning: clean the titanium alloy TC4 metal parts and put them into the vacuum furnace. -3 When Pa, argon gas was introduced, and the metal substrate was cleaned by a linear ion source with a power of 3 kW, a time of 20 min, and a bias voltage of 400 V;

[0066] Step 2, bonding layer deposition: using a titanium target to deposit a bonding Ti layer on the surface of the metal substrate by magnetron sputtering, the titanium target current is 5A, the time is 15min, and the bias voltage is 80V;

[0067] Step 3, gradient transition layer deposition: using titanium target and molybdenum disulfide target magnetron sputtering to deposit gradient transition MoS2-Ti layer, the titanium target current is constant at 2A, and the molybdenum disulfide target current is linearly increased from 0.4A to 3A, the time is 20min, and the bias voltage is 70V;

[0068] Step 4: Deposition of functional layer: Deposition of functional MoS2-Ti layer by magnetron sputtering using titanium target and molybdenum disulfide target, respectively, with constant current of 2A for titanium target and 3A for molybdenum disulfide target, time 90min, bias voltage 70V;

[0069] Step 5: Gradient transition layer deposition: The transition MoS2-Ti-C layer was deposited by magnetron sputtering using titanium target, molybdenum disulfide target and graphite target respectively. The current of the molybdenum disulfide target was constant, the current of the graphite target increased linearly from 0.1A to 1A, and the current of the titanium target decreased linearly from 2A to 0A. The time was 15min and the bias voltage was 70V.

[0070] Step 6, functional layer deposition: the functional MoS2-C layer was deposited by magnetron sputtering using a molybdenum disulfide target and a graphite target, respectively. The molybdenum disulfide target current was constant at 2A, the graphite target current was constant at 1A, the time was 30min, and the bias voltage was 70V.

[0071] The lubricating film deposited in this embodiment has a bright and smooth gray-black coating surface. The three-dimensional optical profilometer test shows that the thickness of the lubricating film is 2±0.2μm, the thickness of the Ti bonding layer is 150±15nm; the thickness of the MoS2-Ti gradient transition layer is 150±15nm; the MoS2-Ti functional layer is 1400±140nm; the MoS2-Ti-C transition layer is 100±10nm, the C content is 16at%, and the Ti content is 15at%; the MoS2-C functional layer is 200±20nm, and the C content is 46at%. Referring to GJB2502.9-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 9: Atomic Oxygen Test", the total atomic oxygen irradiation of the simulated 15-year on-orbit flight on the ground is 7.8×10 26 pcs / m 2 ; Referring to GJB2502.5-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 5: Vacuum Ultraviolet Irradiation Test", the total ultraviolet irradiation is 8000ESH, and a ball-disc friction and wear tester is used. According to GJB3032-97 "Specifications for Sputtered MoS2-based Self-lubricating Solid Films", the friction and wear life in a vacuum environment is 3.6×10 5 r, the friction coefficient is 0.017.

[0072] Example 3

[0073] The method for preparing the adaptive molybdenum disulfide-based multilayer composite film of this embodiment comprises the following steps:

[0074] Step 1: Plasma cleaning: clean the titanium alloy TC4 metal parts and put them into the vacuum furnace. -3 When Pa, argon gas was introduced, and the metal substrate was cleaned by a linear ion source with a power of 2.5 kW, a time of 30 min, and a bias voltage of 400 V;

[0075] Step 2, bonding layer deposition: using a titanium target to deposit a bonding Ti layer on the surface of the metal substrate by magnetron sputtering, the titanium target current is 3A, the time is 20min, and the bias voltage is 80V;

[0076] Step 3, gradient transition layer deposition: using titanium target and molybdenum disulfide target magnetron sputtering to deposit gradient transition MoS2-Ti layer, the titanium target current is constant at 3A, and the molybdenum disulfide target current is linearly increased from 0.4A to 2A, the time is 60min, and the bias voltage is 70V;

[0077] Step 4: Deposition of functional layer: Deposition of functional MoS2-Ti layer by magnetron sputtering using titanium target and molybdenum disulfide target, respectively, with a constant current of 0.8A for titanium target and 1.8A for molybdenum disulfide target, for 90min, and a bias voltage of 70V;

[0078] Step 5: Transition layer deposition: The transition MoS2-Ti-C layer was deposited by magnetron sputtering using titanium target, molybdenum disulfide target and graphite target respectively. The current of the molybdenum disulfide target was constant at 2A, the current of the graphite target was linearly increased from 0.1A to 2A, and the current of the titanium target was linearly decreased from 0.8A to 0A. The time was 60min and the bias voltage was 70V.

[0079] Step 6, functional layer deposition: the functional MoS2-C layer was deposited by magnetron sputtering using a molybdenum disulfide target and a graphite target, respectively. The molybdenum disulfide target current was constant at 1.8A, the graphite target current was constant at 2A, the time was 60min, and the bias voltage was 70V.

[0080] The lubricating film deposited in this embodiment has a bright and smooth gray-black coating surface. Using a three-dimensional optical profilometer to test, the thickness of the lubricating film is 5±0.5μm, the thickness of the Ti bonding layer is 200±20nm; the thickness of the MoS2-Ti gradient transition layer is 600±60nm; the MoS2-Ti functional layer is 2200±220nm; the MoS2-Ti-C transition layer is 1100±110nm, the C content is 30at%, and the Ti content is 6at%; the MoS2-C functional layer is 900±90nm, and the C content is 50at%. Referring to GJB2502.9-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 9: Atomic Oxygen Test", the total atomic oxygen irradiation of the simulated 15-year on-orbit flight on the ground is 7.8×10 26 pcs / m 2 ; Referring to GJB2502.5-2006 1600 "Test Methods for Spacecraft Thermal Control Coatings Part 5: Vacuum Ultraviolet Irradiation Test", after a total ultraviolet irradiation of 8000ESH, a ball-disc friction and wear tester was used, and according to GJB3032-97 "Specifications for Sputtered MoS2-based Self-lubricating Solid Films", the friction and wear life in a vacuum environment was 4.1×10 5 r, the friction coefficient is 0.016.

[0081] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. An adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation, the film structure includes a deposited Ti bonding layer, a MoS2-Ti gradient transition layer, a MoS2-Ti functional layer, a MoS2-Ti-C gradient transition layer and a MoS2-C functional layer in order from near to far from the substrate.

2. The adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation according to claim 1, characterized in that: The film has a thickness of 1 to 5 μm.

3. The adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation according to claim 1, characterized in that: The thickness of the Ti bonding layer is 100 to 500 nm; And / or, the thickness of the MoS2-Ti gradient transition layer is 100 to 1000 nm; and / or, the thickness of the MoS2-Ti functional layer is 200 to 2000 nm; And / or, the thickness of the MoS2-Ti-C gradient transition layer is 50 to 500 nm; And / or, the thickness of the MoS2-C functional layer is 50 to 1000 nm.

4. The adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation according to claim 1, characterized in that: The Ti content in the MoS2-Ti gradient transition layer is 0 to 40 at%; and / or, the Ti content in the MoS2-Ti functional layer ranges from 8% to 20%; And / or, the MoS2-Ti-C gradient transition layer has a C content of 10 to 50 at%, and a Ti content of 5 to 12 at%; And / or, the C content in the MoS2-C functional layer is 40 to 50 at%.

5. A method for preparing an adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1. Plasma cleaning, laser cleaning or high temperature drying cleaning of metal parts; S2, using a titanium target to deposit a Ti bonding layer on the surface of a metal substrate by magnetron sputtering; S3, using titanium target and molybdenum disulfide target to deposit MoS2-Ti gradient transition layer by magnetron sputtering; S4, using a titanium target and a molybdenum disulfide target to deposit a MoS2-Ti functional layer by magnetron sputtering; S5, using titanium target, molybdenum disulfide target and graphite target to deposit MoS2-Ti-C gradient transition layer by magnetron sputtering; S6. Depositing MoS2-C functional layer by magnetron sputtering using molybdenum disulfide target and graphite target.

6. The preparation method according to claim 5, characterized in that: In step S1, the plasma cleaning is performed at a pressure lower than 1×10 -3 Argon gas was introduced under the condition of 1.34 Pa, and the metal substrate was cleaned using a linear ion source.

7. The preparation method according to claim 6, characterized in that: The power of the linear ion source is 2-4 kW, and the cleaning time is 20-60 minutes.

8. The preparation method according to claim 5, characterized in that: In steps S2-S6, the deposition is carried out using closed-field unbalanced magnetron sputtering technology.

9. The preparation method according to claim 5, characterized in that: In step S2, the titanium target current is 0.5 to 5 A, and the deposition time is 10 to 60 min; and / or, in step S3, the titanium target current is constant within the range of 1A to 5A, the molybdenum disulfide target current is linearly increased from 0.1A to 4A, and the deposition time is 10 to 60min; and / or, in step S4, the titanium target current is constant within the range of 1A to 5A, the molybdenum disulfide target current is constant within the range of 1A to 4A, and the deposition time is 10 to 120 min; and / or, in step S5, the molybdenum disulfide target current is constant in the range of 1A to 4A, the graphite target current is linearly increased from 0.1A to 3A, the titanium target current is reduced to 0A, and the deposition time is 2 to 60min; And / or, in step S6, the molybdenum disulfide target current is constant in the range of 1A to 4A, the graphite target current is constant in the range of 0.8 to 3A, and the deposition time is 5 to 120 minutes.

10. Use of the adaptive molybdenum disulfide-based multilayer composite film resistant to low-orbit space radiation as claimed in any one of claims 1 to 4 as a solid lubricant for aerospace materials.

Citation Information

Patent Citations

  • Method for preparing anti-attrition MoS2 / C / Ti composite film by magnetron sputtering

    CN101654771A

  • Self-lubricating antifriction composite thin film based on MoS2-TiC-C and preparation method thereof

    CN101921984A

  • Graphene molybdenum disulfide multilayer wear-resistant coating for aerospace hot work separation and preparation method thereof

    CN109136924A

  • Wear-resistant molybdenum disulfide-based composite film and preparation method thereof

    CN117626179A

Cited By

  • Vacuum wide-temperature-range self-lubricating composite film as well as preparation method and application thereof

    CN121380843A

  • Titanium-doped molybdenum disulfide super-smooth film and preparation method and application thereof

    CN122105308A